2022
DOI: 10.2147/nss.s377946
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Sleep Apnea in Intensive Care Unit Survivors After SARS-CoV-2 Pneumonia

Abstract: Background: Sleep apnea (SA) was reported as possibly exacerbating symptoms of COVID-19, a disease induced by SARS-CoV-2 virus. The same comorbidities are common with both pathologies. This study aimed to estimate the prevalence, characteristics of SA and variation in AHI three months after severe COVID-19 requiring intensive care unit (ICU) admission. Methods: A prospective cohort of patients admitted to ICU for severe COVID-19 underwent an overnight home polygraphy 3 months after onset of symptoms, as part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, many previous studies have claimed that obstructive sleep apnea is an independent risk factor for poor outcomes of COVID‐19 infection, such as higher mortality rate, higher rate of ventilator use and ICU admission due to respiratory failure and longer hospital stay 8,22–26 . There are several mechanisms could explain the finding.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, many previous studies have claimed that obstructive sleep apnea is an independent risk factor for poor outcomes of COVID‐19 infection, such as higher mortality rate, higher rate of ventilator use and ICU admission due to respiratory failure and longer hospital stay 8,22–26 . There are several mechanisms could explain the finding.…”
Section: Discussionmentioning
confidence: 93%
“…Abhishek Goyal et al showed that approximately 73% of moderate‐to‐severe OSA was diagnosed by a PSG in moderate‐to‐severe ARDS in patients with COVID‐19 patients 4–6 weeks after discharge 7 . Ibrahim Traore et al studied 68 cases of patients with severe COVID‐19 who had been admitted to an ICU, and found that 91% of the patients experienced sleep apnea 3 months after the onset of symptoms, with most patients of the obstructive type 8 . In the study by Schwarzl et al 69 COVID‐19 patients, 16 patients (33.3%) were diagnosed with mild OSA, 10 (20.8%) were diagnosed with moderate OSA, and eight patients (16.7%) were diagnosed with severe OSA (AHI ≥ 15).…”
Section: Discussionmentioning
confidence: 99%
“…Compromised respiratory function can lead to a decreased lung capacity, impaired mucociliary clearance and weakened immune response, making individuals more susceptible to respiratory infections like pneumonia. The intermittent hypoxia and oxidative stress associated with OSA can further exacerbate inflammation and tissue damage in the lungs, worsening the severity and outcomes of respiratory illnesses [11,12]. It has also been proven that unrecognized OSA adversely affects patients with COVID-19 pneumonia.…”
Section: Introductionmentioning
confidence: 99%